Economic dynamism, openness, and inclusion how Singapore can make the transition from an era of catch-up growth to life in a mature economy - Hoon, Hian Teck (Advanced research on Asian economy and economics of other continents ;, 2019)
As Singapore progresses from a newly-independent nation to a more mature economy, the economic challenges it faces have evolved. In the 50 years following Singapore's independence, the country tackled economic challenges relating to a fledgling nation, that included launching onto a path of economic take-off, and managing workers' wage aspirations without rising unemployment. It met those challenges, successfully transiting from relative poverty in the 1960s to relative prosperity today. It also serves as a good reference for other emerging economies that, like Singapore, want to avoid the middle-income trap, and for researchers interested in analysing the economic possibilities for current and future Singaporeans.